Phenomenological Hermeneutics and the Study of Literature - Valdes, Mario J. (Book collections on Project MUSE., 1987)
Mario Valdés has taken up the challenge of retracing the historical and philosophical background of his own approach to literature, the application of phenomenological philosophy to the interpretation of texts.